The blood circulation of malignant and benign tumours of the genital interior as a diagnostic tool - Sohn, Christof; Grischke, Eva-Maria; Kaufmann, Manfred; Bastert, Gunther (Onkologie, 1994)
Background: Malignant tumours usually display a blood circulation different from that of benign ones. This fact can be used in sonographic dignity diagnostics. A prerequisite is a technology capable of detecting this difference which becomes evident in the smallest blood vessels, where flow is extremely slow. Patients and Method: The Sonolayer SSH 140A (Toshiba) and the Quantum 2000 (Siemens) devices were used. These systems are in a position to detect slow blood flow in the tissue tested. We examined the very small vessels in the tumour which cannot be identified by black and white ultrasound image but only with the colour Doppler. The colour pixels which we found in or around the tumour in the colour mode were examined with the pulsed Doppler in order to quantify the blood flow. The resistance index (RI) was calculated from systole and diastole. The lowest RI was used for the evaluation. 51 female patients with ovarian tumours (29 malignant, 22 benign), 41 patients with transmutations of the endometrium (25 malignant, 16 benign), 3 patients with sarcoma, 12 patients with myoma and 39 patients with transmutations of the cervix (24 malignant, 15 benign) were preoperatively examined and the result was correlated with the dignity. None of the patients was treated with hormones. Results: The following RI values were measured: ovarian tumours: malignant 41%, benign 77% (premenopause: 45%); endometrial findings: malignant 49%, benign 66% (premenopause: 51%); sarcoma/myoma uteri: sarcoma 33%, myoma 35% (premenopause: 34%); cervical findings: malignant 51%, benign 78% (premenopause: 52%). According to these results the division into premenopause and postmenopause is decisive. As our results demonstrate, differentiation before the menopause is barely possible due to the blood circulation pattern present at this stage, whilst in the postmenopausal status the distinction between benign and malignant tumours becomes highly significant. Conclusion: The organs of the genital interior have physiologically a high circulation of blood in the premenopause. Therefore, the difference between benign and malignant transmutations is low. Thus we can see a significant difference between the blood flow in benign and malignant tumours of the uterus and ovary in the postmenopausal women but no significant difference in the premenopausal woman. The colour Doppler examination is able to improve the dignity diagnostics in postmenopausal women. We could not verify a differentiation between sarcoma and myoma by Doppler examination. If all the restrictions listed are taken into consideration, the blood circulation diagnostics of transmutations of the genital interior in the postmenopause will be able to make an important contribution to dignity diagnostics.
Elektronische Reproduktion der Druck-Ausgabe 11. Mai 2009
Gesehen am 14.02.2024